2016
DOI: 10.1016/j.psyneuen.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological mouse model suggests a novel risk pathway for postpartum psychosis

Abstract: HighlightsPostpartum psychosis (PP) is a severe psychiatric disorder of unknown cause.Steroid sulfatase (STS) deficiency may influence PP risk.Postpartum inhibition of STS in mice results in behavioural and genetic abnormalities.These abnormalities can be alleviated with an antipsychotic drug.The study suggests a new mouse model and a biological risk pathway for PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of psychosis consistent with a diagnosis of early-onset schizophrenia in a child with confirmed XLI. Given the comparative rarity of both XLI and psychosis in the general population, our observations, together with previous literature reporting paranoid schizophrenia in two females with deletions spanning STS [ 22 ] and implicating STS deficiency in postpartum psychosis [ 23 , 24 ], suggest that, in addition to influencing risk of developmental disorders, STS deficiency may also predispose to risk of psychotic illness; this notion is consistent with the latest genome-wide genetic screens which show that individual polymorphisms or mutations may act as risk factors in multiple developmental and affective conditions [ 25 ].…”
Section: Discussionmentioning
confidence: 55%
“…To the best of our knowledge, this is the first report of psychosis consistent with a diagnosis of early-onset schizophrenia in a child with confirmed XLI. Given the comparative rarity of both XLI and psychosis in the general population, our observations, together with previous literature reporting paranoid schizophrenia in two females with deletions spanning STS [ 22 ] and implicating STS deficiency in postpartum psychosis [ 23 , 24 ], suggest that, in addition to influencing risk of developmental disorders, STS deficiency may also predispose to risk of psychotic illness; this notion is consistent with the latest genome-wide genetic screens which show that individual polymorphisms or mutations may act as risk factors in multiple developmental and affective conditions [ 25 ].…”
Section: Discussionmentioning
confidence: 55%
“…The behavioural abnormalities and the Ccn3 overexpression in the mouse model could be attenuated through administration of the antipsychotic drug ziprasidone, supporting its face and predictive validity. The finding that manipulation of placental gene activity in mice gives rise to altered maternal behaviours and increased brain (hippocampal) Ccn3 expression [38] further supports the notion of CCN3 as a mediator of postpartum psychopathology 9 , 36 .…”
Section: A New Hypothesis Reconciling Immune System Dysfunction and Mmentioning
confidence: 63%
“…This new study elegantly demonstrated that Tregs can promote oligodendrocyte differentiation and (re)myelination within the CNS independently of inflammatory processes via secretion of the protein CCN3 (also known as nephroblastoma-overexpressed protein, or NOV) [35] . This finding was of particular interest to us given that the CCN protein family member CCN3 had been suggested as a candidate mediator of PP risk by our work in a novel pharmacological mouse model [36] . In our model, Ccn3 expression was upregulated in whole brain tissue from new mouse mothers acutely administered an inhibitor of steroid sulfatase (to mimic the putative PP risk factor maternal steroid sulfatase deficiency [37] ); these mice exhibited abnormal postpartum anxiety-related and startle behaviours of possible relevance to PP.…”
Section: A New Hypothesis Reconciling Immune System Dysfunction and Mmentioning
confidence: 69%
“…Expression screening of the small number of genes within the mouse chromosome 15 interval revealed just one, Nov / Ccn3 , whose expression was significantly altered (upregulated) in STS-inhibited brain; the expression of two other genes from the Ccn family ( Ctgf/Ccn2 and Wisp1/Ccn4 ), as well as genes whose products may be co-regulated with Nov/CCN3 ( Arhgdig , Adcy8 and Ccl2 ) was also increased in STS-inhibited brain tissue[54]. …”
Section: Insights From a New Mouse Modelmentioning
confidence: 99%
“…We showed that administration of clinically-relevant doses of the atypical antipsychotic ziprasidone reverses the deficient startle response, and tempers the over-expression of Nov/Ccn3 in the STS-inhibited mouse, indicating that these facets of the model may be relevant to psychotic pathophysiology[54]. …”
Section: Insights From a New Mouse Modelmentioning
confidence: 99%